2010
DOI: 10.1186/1475-2875-9-163
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in access to malaria treatment in Tanzania following community, retail sector and health facility interventions -- a user perspective

Abstract: BackgroundThe ACCESS programme aims at understanding and improving access to prompt and effective malaria treatment. Between 2004 and 2008 the programme implemented a social marketing campaign for improved treatment-seeking. To improve access to treatment in the private retail sector a new class of outlets known as accredited drug dispensing outlets (ADDO) was created in Tanzania in 2006. Tanzania changed its first-line treatment for malaria from sulphadoxine-pyrimethamine (SP) to artemether-lumefantrine (ALu)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 38 publications
1
62
1
Order By: Relevance
“…These data support the findings of a 2008-9 survey in other parts of Tanzania, showing that SP still accounted for three quarters of the sale of anti-malarials in private drug shops [26]. Even in Morogoro region, where the ADDO programme is already implemented, 65% of anti-malarial customers received SP, and only 13% received ALu [27]. The present study has shown that, although ACT is available in private shops, it is only accessed by a minority of the population.…”
Section: Discussionsupporting
confidence: 85%
“…These data support the findings of a 2008-9 survey in other parts of Tanzania, showing that SP still accounted for three quarters of the sale of anti-malarials in private drug shops [26]. Even in Morogoro region, where the ADDO programme is already implemented, 65% of anti-malarial customers received SP, and only 13% received ALu [27]. The present study has shown that, although ACT is available in private shops, it is only accessed by a minority of the population.…”
Section: Discussionsupporting
confidence: 85%
“…The area is covered by 13 public and private health facilities (11 dispensaries and 2 health centres) with 55 and 135 ADDOs in Ulanga and Kilombero districts respectively [4]. …”
Section: Methodsmentioning
confidence: 99%
“…The World Health Organization (WHO), therefore, recommends home-based management of malaria (HMM) as a means to increase access to prompt and effective treatment of malaria [2]. Bringing treatment closer to home through the implementation of HMM should improve access to malaria case management services in areas with scarce health facilities and qualified human resources, as is typically found in rural Africa [3-5] . A number of studies, some of them conducted under the leadership of the WHO, have demonstrated its feasibility and efficacy [6-9], and several studies have evaluated the introduction of ACT through HMM programmes [10,11].…”
Section: Introductionmentioning
confidence: 99%